2013
DOI: 10.3109/01612840.2012.740768
|View full text |Cite
|
Sign up to set email alerts
|

Does Education Improve Mental Health Practitioners’ Confidence in Meeting the Physical Health Needs of Mental Health Service Users? A Mixed Methods Pilot Study

Abstract: Mental health nurses are ideally placed to assess mental health service users' physical health and provide relevant interventions. However, they may lack the confidence and knowledge to do so, as a result of limited education on physical health issues. This mixed methods pilot study sought to evaluate the effect of education on confidence in assessing and addressing physical health needs following attendance at a module entitled "Physical health issues in adult mental Health practice." An explanatory sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Worthy of further consideration is that virtually all participants rated themselves to be 'very satisfied' or 'satisfied' with the workshops. This concords with research conducted by Terry and Cutter (2013) who undertook and pre-test and post-test analysis of MHNs undertaking a postgraduate module on physical health interventions. Satisfaction with education experience has been highlighted as a motivating factor for nurses working with mental health service users, and this in turn improves their therapeutic optimism (Edward et al 2011a, Hemingway et al 2013b).…”
Section: Discussionmentioning
confidence: 89%
“…Worthy of further consideration is that virtually all participants rated themselves to be 'very satisfied' or 'satisfied' with the workshops. This concords with research conducted by Terry and Cutter (2013) who undertook and pre-test and post-test analysis of MHNs undertaking a postgraduate module on physical health interventions. Satisfaction with education experience has been highlighted as a motivating factor for nurses working with mental health service users, and this in turn improves their therapeutic optimism (Edward et al 2011a, Hemingway et al 2013b).…”
Section: Discussionmentioning
confidence: 89%
“…The positive association results are consistent with previous research undertaken within Canadian community mental health care workers [ 26 ] and UK psychiatric inpatient nurses [ 27 ], whereby attitudes regarding role congruence, confidence in care provision, and client interest were associated with the self-reported provision of preventive care. Training and educational resources have been found to improve clinician attitudes and confidence towards providing physical health care to people with a mental illness [ 54 , 61 ], and the current results suggest that such strategies addressing negative attitudes may be required to increase preventive care provision.…”
Section: Discussionmentioning
confidence: 95%
“…Findings from that review indicated that the attitudes of clinical staff toward providing metabolic health care in mental health settings was integral to the successful delivery of such services ( 14 , 15 , 19 , 27 , 28 ). Another common finding was a low level of confidence among mental health staff in carrying out recommended metabolic health monitoring and delivering interventions ( 15 , 16 , 18 , 32 ), in addition to a lack of knowledge in this area ( 15 , 33 , 34 ). Other consistent barriers to staff delivering metabolic care were workload, concerns regarding medication adherence, perceived apathy on the part of a service user or a sense of hopelessness from a staff member ( 15 , 16 , 18 , 19 , 27 , 28 , 33 – 35 ).…”
Section: Methodsmentioning
confidence: 99%